2022
DOI: 10.1002/smll.202202072
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Electron Donor for Conjugated Microporous Polymer Photocatalysts with High Photocatalytic Hydrogen Evolution Activity

Abstract: electronic structure. [3][4][5] Nevertheless, most inorganic photocatalysts suffer from low activity under visible light, complexity in the preparation, and the limited natural resources. Recent studies demonstrated that organic semiconductors could be a promising class of photocatalysts for hydrogen evolution because of their diverse structures, various synthetic strategies, and tunable electronic properties. [6][7][8] To date, various organic polymers with conjugated skeletons have been developed as photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…It has been reported that the longer the π-electron conjugated system, the better charge separation and transfer efficiency. 56,78,84 Together, these findings confirmed that our Py-CMPs had good ability to separate and transfer photogenerated electrons under illumination.…”
Section: Polymer Chemistry Papersupporting
confidence: 72%
“…It has been reported that the longer the π-electron conjugated system, the better charge separation and transfer efficiency. 56,78,84 Together, these findings confirmed that our Py-CMPs had good ability to separate and transfer photogenerated electrons under illumination.…”
Section: Polymer Chemistry Papersupporting
confidence: 72%
“…The photocatalytic H 2 generation experiment was conducted on an all-glass automatic online trace gas analysis system (Labsolar-6A, Beijing Perfectlight Technology Co., Ltd.) according to our previously reported procedures. 34…”
Section: ■ Introductionmentioning
confidence: 99%
“…Meanwhile, the high price and limited precious metal resources increase the cost of this technology and hinder its large-scale application and promotion. Therefore, many scholars have gradually turned their attention to the photocatalytic hydrogen evolution technology, [12][13][14][15] which is a low-energy consumption and environmentally friendly method. In addition, the technology is easier to build and expand.…”
Section: Introductionmentioning
confidence: 99%